Abdurrahman Wahid's Thoughts on Human Rights Based Humanistic Education in Indonesia - Iskandar Sulaemani; Iyad Suryadi; Helmawati (Jurnal Visionary : Penelitian dan Pengembangan dibidang Administrasi Pendidikan, 2025)
This study aimed to analyze K.H. Abdurrahman Wahid's thoughts on human rights-based education within the framework of Islamic humanism and to identify obstacles to its implementation in the context of national education. Using a qualitative literature review approach, data were obtained through a review of Gus Dur's works and related academic literature. The results indicate that Gus Dur's thoughts emphasize the importance of inclusive, democratic education based on respect for diversity. Three main findings were identified: a lack of understanding of human rights values among teachers, conventional teaching methods that minimize student participation, and a social environment that does not support the spirit of inclusion. Additionally, inclusive learning strategies and educational environments have been shown to play a significant role in increasing students' awareness of human rights values. Gus Dur stated that education is a means of humanising humans, not merely a tool for reproducing knowledge. Therefore, human rights-based education must be realized systematically through curriculum reform, teacher training, and collaboration between schools and the community. This study contributes to the development of an educational model that is responsive to social justice and diversity in Indonesia. Keywords: Abdurrahman Wahid, Human Rights, Humanistic Education. Abstrak: Penelitian ini bertujuan untuk menganalisis pemikiran K.H. Abdurrahman Wahid (Gus Dur) mengenai pendidikan berbasis hak asasi manusia dalam kerangka humanisme Islam, serta mengidentifikasi hambatan dalam implementasinya dalam konteks pendidikan nasional. Pendekatan tinjauan literatur kualitatif digunakan, dengan data diperoleh melalui analisis karya-karya Gus Dur dan literatur akademik terkait. Hasil penelitian menunjukkan bahwa pemikiran Gus Dur menekankan pentingnya pendidikan inklusif dan demokratis yang didasarkan pada penghormatan terhadap keragaman. Tiga temuan utama diidentifikasi: kurangnya pemahaman nilai-nilai hak asasi manusia di kalangan guru, metode pengajaran konvensional yang meminimalkan partisipasi siswa, dan lingkungan sosial yang tidak mendukung semangat inklusi. Selain itu, strategi pembelajaran inklusif dan lingkungan pendidikan telah terbukti memainkan peran penting dalam meningkatkan kesadaran siswa terhadap nilai-nilai hak asasi manusia. Gus Dur menyatakan bahwa pendidikan adalah sarana untuk menghumanisasi manusia, bukan sekadar alat untuk mereproduksi pengetahuan. Oleh karena itu, pendidikan berbasis hak asasi manusia harus diwujudkan secara sistematis melalui reformasi kurikulum, pelatihan guru, dan kolaborasi antara sekolah dan masyarakat. Studi ini berkontribusi pada pengembangan model pendidikan yang responsif terhadap keadilan sosial dan keragaman di Indonesia. Kata kunci: Abdurrahman Wahid, Hak Asasi Manusia, Pendidikan Humanis.